Single-step affinity purification of recombinant proteins using a self-excising module from Neisseria meningitidis FrpC - Sadilkova, Lenka; Osicka, Radim; Sulc, Miroslav; Linhartova, Irena; Novak, Petr; Sebo, Peter (Protein science, 2008)
Purification of recombinant proteins is often a challenging process involving several chromatographic steps that must be optimized for each target protein. Here, we developed a self-excising module allowing single-step affinity chromatography purification of untagged recombinant proteins. It consists of a 250-residue-long self-processing module of the Neisseria meningitidis FrpC protein with a C-terminal affinity tag. The N terminus of the module is fused to the C terminus of a target protein of interest. Upon binding of the fusion protein to an affinity matrix from cell lysate and washing out contaminating proteins, site-specific cleavage of the Asp-Pro bond linking the target protein to the self-excising module is induced by calcium ions. This results in the release of the target protein with only a single aspartic acid residue added at the C terminus, while the self-excising affinity module remains trapped on the affinity matrix. The system was successfully tested with several target proteins, including glutathione-S-transferase, maltose-binding protein, beta-galactosidase, chloramphenicol acetyltransferase, and adenylate cyclase, and two different affinity tags, chitin-binding domain or poly-His. Moreover, it was demonstrated that it can be applied as an alternative to two currently existing systems, based on the self-splicing intein of Saccharomyces cerevisiae and sortase A of Staphylococcus aureus.
Keywords: Bacterial Proteins; rekombinantní proteiny; Calcium; vápník; Protein Structure, Tertiary; membránové proteiny; chromatografie afinitní; kyselina asparagová; Membrane Proteins; Aspartic Acid; Chromatography, Affinity; bakteriální proteiny; terciární struktura proteinů; Recombinant Proteins